UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PICTURE AND PICTURE BERBANTUAN BENDA KONKRET PADA SISWA KELAS III DI SEKOLAH DASAR - Fadzilatun Nikmah, Maulida (Jurnal Pendidikan Dasar, 2017)
Abstract : This study was conducted as an effort to improve the learning process of thelearning outcomes are not optimal in Class III Elementary School District of TuntangCandirejo second semester of the school year 2016/2017. This study aims to determinewhether the results of learning mathematics can be improved through the model Pictureand Picture. This type of research i PTK, which was done 2 cycles. Subjects consisted of25 students of class III.Data collection techniques include test and non-test techniques(observation). The results showed an increase in Math learning outcomes Flat materialbetween the pre-cycle, the first cycle and the second cycle is based on 1) Complete 36% inpre-cycle to 48% in the first cycle to 92% in the second cycle; 2) The mean score on thepre-cycle increase in cycle I 64.06 68.04 into 80.16 on the second cycle; 3) The maximumscore on the pre-cycle 75 to 80 in the first cycle to 90 in the second cycle; 4) Score precycleminimum50to55inthefirstcycleto65inthesecondcycle.SimpulanyaPictureand Picture model application is successful because it achieves performance indicators ie92.1% â‰¥ 80% of all students completed with KKM â‰¥ 70. Keywords: learning outcomes, learning model Picture and Picture